Recent trends in aortic valve interventions: Data of the Netherlands heart registration. Issue 2 (23rd December 2020) - Daeter, Edgar J.; van Veghel, Dennis; Houterman, Saskia; Olsthoorn, Jules; Soliman‐Hamad, Mohamed A.; ,
Abstract: Background and Aim of the Study: Transcatheter aortic valve implantation (TAVI) has evolved from bailout for inoperable patients to an alternative to surgical aortic valve replacement (SAVR) in higher‐risk groups. The aim of this study is to describe these clinical trends in TAVI and SAVR in patients with aortic valve disease. Methods: We analyzed data of the Netherlands Heart Registration (NHR) up to 2018 to explore the trends in TAVI and SAVR among 14 cardiac centers in the Netherlands. Results: Between 2013 and 2017, a total of 7432 isolated SAVR and 5929 TAVI procedures have been performed. A 43.9% increase in the total number of procedures was observed, mainly due to the considerable increase in the number of TAVI procedures. In 2017, there was a decrease in the number of SAVR procedures. In the TAVI group, 30‐ and 120‐day mortality decreased significantly from 7.2% and 10.6% in 2013 to 3.4% and 5.7% in 2017, respectively. In the SAVR group, 30‐ and 120‐day mortality decreased from 1.7% and 2.9% in 2013 to 1.2% and 1.7% in 2017, respectively. Outcomes showed a significant decrease in vascular complications after TAVI. The risk profile of TAVI patients has changed over time. Conclusions: The recent developments in TAVI have contributed to the increasing numbers of aortic valve interventions in the Netherlands. Mortality rates after SAVR and TAVI decreased as did the rate of complications after TAVI. Furthermore, a trend towards decrease of preoperative risk was observed.